Alokasi Dana Desa (ADD), Jumlah Penduduk Miskin, Indeks Pembangunan Manusia (IPM) Dan Pertumbuhan Ekonomi - Yulius Laga; Anthonia Karolina Rejo Lobwaer (Universitas Musamus,Merauke,Papua, 2020)
This paper is a form of concept development, with the variable allocation of village funds (X1), the number of poor people (X2), Human Development Index (X3) and Economic Growth (Y) in East Nusa Tenggara Province in 21 districts. This study uses secondary data obtained from the Central Statistics Agency (BPS) of NTT Province from 2015 to 2019. Descriptive Statistics and Panel Data Regression Analysis using E-Views 10 using the Fixed Effect Model (FEM). The results of hypothesis testing (t-test) shows the allocation of village funds, has a positive and significant effect on Economic Growth (p-value: 0,000 <0.05) and (t-count = 7.81> t-table = 1.66) . While the number of poor people and the Economic Human Development Index (HDI) have no influence on Economic Growth because the probability value is more than 5 percent (0.05). The magnitude of the effect of Adjust R-Square (R2) of 0.35 or 35 percent of economic growth variables can be explained by the variable Village Fund Allocation, Number of Poor Population, and Human Development Index. This reflects the economy grows to be done, and not only from the Village Fund Allocation but has investment space in the priority sectors of each district that is able to reduce poverty and boost the Human Development Index.